Three new polycyclic containing sulfur compounds from the seeds of Combretum quadrangulare kurz (Combretaceae), antifungal and anti-mycobacterium activities - Khesorn Nantachit (2018)
© 2017, Chiang Mai University. All rights reserved. Three new polycyclic containing sulfur compounds, Combretanoid, Combretanane and Combretanun, were isolated. The crude ethanolic extract and pure compound Combretin, the isolated pure compound from the seeds of Combretum quadrangulare Kurz (Combretaceae), showed antimicrobial activities against many pathogens. The aim of this study was to determine antifungal activity against opportunistic pathogens in HIV patients and anti-mycobacterium tuberculosis activity (anti-TB). An Antifungal test was performed by agar dilution method and an anti-TB test was done using green fluorescent protein microplate assay (GFPMA). Crude ethanolic extract from Amphur Sun Srai showed antifungal activity against A. fumigatus better than the extract from Amphur Sarapee. Combretanoid showed no antifungal activity and the three new compounds showed no anti-TB activity. This plant showed no toxicity to albino rat and mice. In conclusion, it may used as a traditional method for antifungal activity against A. fumigatus.